Respuesta :
Answer:
The general formula that represents the given sequence is:
[tex]f(x)=-\dfrac{2}{3}\times 6^x[/tex]
Step-by-step explanation:
We are given a sequence as:
−4, −24, −144,...
The first term is:
-4.
second term is:
-24 and so on.
So, looking at the sequence the general formula that can be formed is:
[tex]f(x)=-\dfrac{2}{3}\times 6^x[/tex]
Hence, the first term i..e when x=1 we have:
[tex]f(1)=-\dfrac{2}{3}\times 6\\\\f(1)=-2\times 2\\\\f(1)=-4[/tex]
Similarly the second term i.e. when x=2 we have:
[tex]f(2)=-\dfrac{2}{3}\times 6^2\\\\f(2)=-24[/tex]
and so on.
Hence, the general formula is:
[tex]f(x)=-\dfrac{2}{3}\times 6^x[/tex]